Implementation of the Pedagogic Competence of Islamic Religious Education Teachers - Ananda, Fauzi (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to bridge the gap in the literature by providing insight into the effectiveness of an integrative approach to improve the pedagogical competence of IRE teachers. In addition, this research will explore existing IRE teacher pedagogic practices in a contemporary context, which will provide valuable information for educational institutions and policy makers wishing to develop an effective IRE pedagogy. Therefore, the results of this study will provide significant benefits for IRE teachers and their students, educational institutions, and the wider community. Methodology:This research uses the literature study method which relies on bibliographic sources from books and articles in scientific journals related to the subject matter, reading data with the thoughts of experts with a constructive approach and interpretation of the main content. Main Findings: Recognizing the importance of the quality of human resources itself, the government and the private sector have and continue to work together to realize this mandate through various efforts to develop higher quality school education, including: (1) curriculum development and improvement, (2) evaluation system improvement , (3) improvement of educational facilities, (4) development and procurement of teaching materials, (5) training of teachers and other education personnel. Novelty/Originality of this study: The learning process and student learning outcomes are not only determined by the school, pattern, structure and content of the curriculum, but are determined by the competence of the teachers who teach and guide them. Competent teachers will be better able to create an effective, enjoyable learning environment, and be better able to manage their classes, so that student learning is at an optimal level.